Treating co-occurring disorders in jails: outcome findings from a second chance act offender reentry program - Miller, J. Mitchell (Crime & delinquency, 2019)
Widespread implementation of offender reentry programming has increased justice program evaluations but few have featured research designs sufficiently rigorous to optimally inform policy. Program evaluations typically neglect program fidelity concerns to focus on outcome analysis that seldom feature optimal spuriousness reduction. The current study, the second component of a mixed-method design evidencing fidelity, presents the methods and outcome findings for the Delaware County Transition (DCT) Program, an Ohio jail-based crimesolutions.gov endorsed treatment intervention for dually diagnosed offenders. Review of the reentry and dual-diagnosis literature provides a background for description of the DCT program and methods employed to observe programming effects. Findings indicated DCT participation was associated with overall recidivism reductions and time to recidivism and orient discussion around related rehabilitative modalities.